The Impact of Social Media and Artificial Intelligence Use on Students’ Character in Civic Education Learning - FAIZAH HIJRIATI; SAPRIYA; ADE BUDHI SALIRA; DADANG SUNDAWA (Universitas PGRI Kanjuruhan Malang, 2026)
The digital transformation has ushered society into an era of disruption, triggering a digital moral crisis among Generation Z. This study aims to synthesize contemporary pedagogical frameworks to develop an integrative model of Digital Ethics-Based Civic Education that incorporates social media and Artificial Intelligence literacy to strengthen national character and students' moral resilience. Adopting a qualitative approach through a literature review, data were collected from reputable national and international journals and official government reports from 2020 to 2025. The research findings indicate that technical proficiency alone is insufficient to preserve moral integrity without a strong ethical anchor. A reorientation of pedagogical strategies is necessary by integrating the Pancasila Student Profile, strengthening interpersonal intelligence, and utilizing innovative technologies such as Artificial Intelligence and social media as tools for active value learning. The conclusion of this study emphasizes that the future of Civic Education depends on its transformation into a living curriculum that positions educators as moral navigators in the digital space to foster smart and good citizens.